G311 How exactly does integrated paediatric care work? A theoretical research framework. (27th April 2016) - Blair, M; Watson, M; Klaber, R; Woodcock, T
Abstract : Background: Many areas in the UK are experimenting with different models of care delivery to improve integration of services and experiences of children young people and their carers. One such initiative "Connecting Care for Children" (CC4C) is based on three key components:- specialist outreach to a number of GP "hubs", open access for advice and referrals and public and patient engagement. Robust evaluation of such health system change is desirable but often complex to conceptualise and achieve. Aim: To develop an agreed conceptual framework to facilitate measurement of the quality of health system delivery in a defined population and to support research on proposed mediating factors. Methods: A number of methods were used including stakeholder mapping, experiential "word cloud" capture, and "Action Effect Diagram" (AED) development. 1 Engagement of staff, patients and young people at a number of collaborative events over a two year period. A joint workshop with academics from a number of institutions helped to refine specific measures and identify gaps in current knowledge. Over 100 individuals have been involved in drawing up the final model. Results: Word cloud highlighted clinical and organisational issues (See Figure 1 ). There was considerable consistency across populations. An AED was developed over a series of iterations which elucidated the possible theoretical mechanisms for cause and effect of the three key components of the CC4C model. This was subsequently redrawn in a standardised logic model format to aid understanding (Figure 2 ). We have highlighted those elements which we believe are common to all such developments in integrated care and those which are for local determination and adaptation. Potential metrics for each of these segments are highlighted in Table 1 . Conclusions: We found a high degree of agreement for a conceptual framework which explains how integrated care processes might be mediated. Local academics and commissioners alike have found these developments invaluable in understanding and building a picture of how integrated care can be operationalized and researched. Regular stakeholder reiteration of such diagrams is important in both ensuring ownership and investment in the inputs required. Reference: 1 Reed JE, et al . BMJ Qual Saf 2014; 0:1–9. doi:10.1136/bmjqs-2014-003103